The Role of Oxidative Stress in the Aging Process - Barbara F. Oliveira; José Augusto Nogueira-Machado; Míriam M. Chaves (The Scientific World Journal)
The aging of organisms is characterized by a gradual functional decline of all organ systems. An appropriate theory must explain four main characteristics of aging: it is progressive, endogenous, irreversible, and deleterious for the individual. The aging of the immune system, or immunosenescence, is manifested by an increased susceptibility to infections with increased morbidity and mortality. Phagocytic capacity, synthesis of reactive oxygen intermediaries, and the intracellular killing efficiency of neutrophils are impaired in the elderly. Among all aging theories, the most updated one describes the free radicals. It implies that progressive aging is associated with higher levels of oxidative biomolecules reacted with free radicals. Although reactive oxygen species (ROS) are predominantly implicated in causing cell damage, they also play a major physiological role in several aspects of intracellular signaling and regulation. ROS include a number of chemically reactive molecules derived from oxygen. Not only oxygen, but also nitrogen can be deleterious species. The overproduction of reactive nitrogen species (RNS) is called nitrosative stress. ROS/RNS are known to play a dual role in biological systems since they can be either harmful or beneficial to living systems.